THE TITLE - THE FIRST WORD THAT THE AUTHOR SAYS TO HIS READER - Jurayeva Maqsuda; Tulabayeva Madina (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the functions of headlines in the press, creating good headlines, better understanding the strategy of using figures of speech in headlines in the French press, and the differences between paper and online versions of newspaper headlines.